Impact load and mechanical respond of tibiofemoral joint - Oshkour, A.A.; Abu Osman, Noor Azuan; Davoodi, M.M.; Bayat, M.; Yau, Y.H.; Wan Abas, Wan Abu Bakar (2011)
Mechanical respond of the tibiofemoral joint in impact with a rigid plate is the aim of current study. A circular plate with initial velocity hit the tibiofemoral joint. All components all considered as linear elastic material. Cartilages were perfectly attached to the femur and tibia; and while menisci were allowed to move vertically. Circular plate motion was vertically. Femur and tibia if they were target of rigid plate they left free for motion vertically; otherwise, they were fixed at the end. Computed tomography images were used to construct 3-dimentional model of the tibiofemoral joint to analysis in the commercial finite element software package ABAQUS v6.7. We found that during impact depend on the velocity of impactor the contact pressure increased from 0 to maximum value and again descend to 0. Moreover, the maximum contact pressures occur with small time delay in knee joint due to the nature of impact. Regardless types of loading the results were same with some percentage difference.